Green Information Technology Strategies for Promoting Sustainable Development Practices among Kirkuk University Affiliates in Iraq - Ayad Fadhil Mohsin (Studi Akuntansi dan Bisnis Indonesia, 2026)
Purpose: This study aims to examine the effect of Green Information Technology strategies on sustainable development and to analyze the relationship between them. Methodology: The study used a descriptive-analytical method with data collected through an electronic questionnaire distributed to administrative and human resource employees at governmental universities in Kirkuk Governorate. Results: The study found that Green Information Technology strategies play an important role in supporting sustainable development within governmental universities. The findings indicate that the adoption of environmentally friendly information technology practices can improve institutional efficiency, reduce environmental impact, and support sustainable administrative performance. Conclusions: The study concludes that Green Information Technology contributes positively to achieving sustainable development in governmental universities in Kirkuk Governorate. The relationship between Green Information Technology and sustainable development shows that universities can strengthen sustainability by integrating green technology practices into their administrative and operational activities. Limitations: This study is limited to governmental universities in Kirkuk Governorate and focuses only on administrative and human resource employees. Contribution: This study contributes by highlighting the role of Green Information Technology strategies in supporting sustainable development practices in higher education institutions.